Discourse Configuration of the Social Upsurge in Three Chilean Cyberpress Media [Construcción Discursiva del "Estallido Social" en Tres Medios de Ciberprensa Chilena] - Farias-Farias, M; Araya-Seguel, C (Universidad de la Serena,Departamento de Artes y Letras, 2022)
This paper reports on some preliminary findings from the research project Ideological conceptions about the Chilean constitutional process (2021). Results from the linguistic valorative analysis of cyberpress texts and their rethorical effects dealing with the Social Upsurge, the foundational event of the constitutional process, are presented. These results show that El Mostrador assumes a critical position towards the government by thematizing the following: "a defeated government", "the opposition s accusation" and "the government as dictatorship". The cyber newspaper Emol takes a critical look at violence and its consequences to the Santiago subway through the themes "the chaos of evasion", "the subway s relevance" and "the sharing of guilt". In turn, La Tercera thematizes violence and highlights the government s measures against it. The semantic polarization and the actors represented in the texts constitute a discourse territory of ideological tensions and alignements. © 2022 Logos: Revista de Linguistica, Filosofia y Literatura. All right reserved.